2012
DOI: 10.1111/j.1875-595x.2011.00082.x
|View full text |Cite
|
Sign up to set email alerts
|

A survey on oral health status and treatment needs of life-imprisoned inmates in central jails of Karnataka, India

Abstract: This study emphasises the need for special attention from government and voluntary organisations to improve the oral health of inmates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
54
3
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(69 citation statements)
references
References 19 publications
10
54
3
2
Order By: Relevance
“…[8] Although a good number of participants in the present study had missing teeth, more had untreated decayed teeth similar to findings of other studies. [1420] We found one inmate with all his teeth missing, an observation that also featured prominently in related studies. [111920] The challenges posed by total loss of all teeth in the mouth such as problems with feeding, communication and general well-being could be minimized if the missing teeth are replaced with dentures.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…[8] Although a good number of participants in the present study had missing teeth, more had untreated decayed teeth similar to findings of other studies. [1420] We found one inmate with all his teeth missing, an observation that also featured prominently in related studies. [111920] The challenges posed by total loss of all teeth in the mouth such as problems with feeding, communication and general well-being could be minimized if the missing teeth are replaced with dentures.…”
Section: Discussionsupporting
confidence: 66%
“…Availability and accessibility of oral health-care services for prisoners in other countries either partially or totally is well-documented. [111920] In Australia, inmates with a low security classification usually receive treatment in local facilities under escort from custodial staff, whereas inmates with a more restrictive security classification are transported to a dental hospital through a Long Bay Prison. [11] Regular dental care services are available for inmates of Bangalore and Mysore central jails in India and for inmates of Calabria, southern Italy too.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the scarcity of studies limits the knowledge about the oral health conditions of prisoners, international findings [36] have shown that prisoners, in general, exhibit unsatisfactory oral conditions, especially with regard to the large number of missing teeth and with untreated caries, justified by social exclusion and unemployment experienced prior to prison [7], associated with irregular use of dental services and use of drugs [8]. …”
Section: Introductionmentioning
confidence: 99%
“…This could be attributed to inadequate prison health care services, lack of dental awareness, and differences in the diet consumption of the prisoners. 27 Furthermore, the oral health services are provided only in emergency situation rather than routine checkups. This also supports the fact that the oral health status of juvenile prisoners is worse than the general population and is well supported by previous reported studies about oral health care services in prison.…”
Section: Discussionmentioning
confidence: 99%